Maine Libraries: An Update on Sharing and Collaboration - Cundick, Bryce; Sanborn, James (Maine Policy Review, 2024)
In Maine Policy Review’s 2013 special issue on libraries, David Nutty and James Jackson Sanborn gave a strong overview of the collaboration between libraries in the state from the early 1900s to the then-present day. However, over the following years, several significant changes have occurred in Maine’s library landscape, which we will cover in this update.